False alarm rates of liquid explosives detection systems - Dzhongova, Elitsa; Anderson, David; de Ruiter, Jaap; Novakovic, Velibor; Ruiz Oses, Miguel (Journal of Transportation Security, 2017)
Restrictions on the carriage of liquids, aerosol, and gels (LAGs) by airline passengers have been in place since November 2006, following the discovery of a terrorist plot involving homemade liquid explosives to be used on transatlantic flights (Wikipedia, 2006). Restrictions on the carriage of LAGs remain today, and the operational impact of introducing further screening of liquids is subject to ongoing debate. This paper addresses one of the concerns, namely that the false alarm rates of liquid explosive detection systems (LEDS) are adversely affected by the filling level of LAGs containers. Our study contributes to a better understanding of the operational impact of screening partially full containers, based on a large number of screening repetitions under laboratory conditions and robust statistical analysis. False alarm rates were observed for 39 LAGs screened with 5 different LEDS. For each combination, four different container filling levels (100%, 75%, 50% and 25%) were studied. These observations were used to model the impact of partially filling for sequential combinations of equipment. Three possible scenarios were considered, namely passengers being allowed to carry (1) only water, (2) water & soft drinks, and (3) all LAGs. The results show that, for a sequential combination of two equipment types, the impact of partially filled containers on the overall false alarm rate is negligible. Nevertheless, partially filled containers do result in an approximate two-fold increase in the number of items requiring level-two screening, which may be significant for airports when managing their screening processes.